Locke on Persons and Personal Identity by Ruth Boeker - Haywood, Joshua Harry (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2023)
A review of Ruth Boeker’s recent book Locke on Persons and Personal Identity (Oxford: Oxford University Press, 2021).